EKSPLORASI SIKAP SOPAN SANTUN DALAM INTERAKSI LINGKUNGAN SISWA KELAS IV SEKOLAH DASAR DI KOTA CIREBON - Restiani, Mawita; Siti Nur Istiqomah; Qorina Ammara; Suherli Kusmana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to explore the politeness attitudes of fourth-grade elementary school students in social interactions and identify the factors influencing these attitudes. This research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation in three elementary schools in Cirebon City, namely SDN 1 Kedawung, SDN Kartini 1, and SDN Kartini IV. The findings indicate that students demonstrate relatively good levels of polite behavior in communication, respect toward teachers, cooperation with peers, compliance with school rules, and the use of polite expressions. However, inappropriate behavior is still observed in informal situations, and the application of polite expressions is not yet fully consistent among students. Students’ polite behavior is influenced by teacher role modeling, family environment, peer interaction, and the use of digital media. In addition, school programs such as the 5S culture and character habituation also contribute to the development of these behaviors. Overall, students’ politeness is shaped through the interaction of various factors within both school and social environments.